Lower Silesia looks to the future. The project of Wrocław - Kłodzko county motorway (1927–1932) as part of the provincial authorities' modernization plan - Przerwa, Tomasz (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2019)
The article presents the fate on an unrealized plan to build the Wrocław – Kłodzko County motorway (1927–1932), which was to connect the capital of Lower Silesia with the Sudetes. It was the object of discussion of regional authorities responsible for modernization of the road network of the Province of Lower Silesia.
Keywords: history of industry; road construction; history of Silesia; Weimar Republic